Modelling positive consequences: Increased vegetable intakes following modelled enjoyment versus modelled intake. (1st September 2019) - Appleton, K.M.; Barrie, E.; Samuel, T.J.
Abstract: Objective: Modelling has previously been demonstrated to encourage healthy eating, but the importance of modelling the behaviour versus modelling the positive consequences of the behaviour is unknown. This work investigated the impact of modelling carrot intake (the behaviour) and modelling carrot enjoyment (the positive consequences) on subsequent liking and consumption of carrots and sweetcorn. Methods: 155 children aged 7–10 years were randomized to hear a story where fictional characters consumed a picnic with either: no mention of carrot sticks (control) (N = 45); mention of carrot sticks that all characters ate (modelling intake) (N = 60); or mention of carrot sticks that the characters like (modelling enjoyment) (N = 50). Carrot and sweetcorn liking and intake were measured before and after the story during a 5 min task. Results: Carrot liking and intake after a story were higher following the story modelling carrot enjoyment compared to the stories not modelling enjoyment (smallest β = 0.16, p = 0.05), and in those with higher pre-story carrot liking and intake (smallest β = 0.25, p < 0.01). Sweetcorn liking and intake after a story were associated with pre-story sweetcorn liking and intake (smallest β = 0.28, p < 0.01), and sweetcorn intake was lower following the story modelling carrot enjoyment compared to the stories not modelling enjoyment (β = −0.17, p = 0.04). Conclusions: These findings demonstrate a role for modelling enjoyment to encourage vegetable liking and intake, although effects sizes were small. These findings also suggest a benefit from modelling the positive consequences of a behaviour for encouraging healthy food intake in children, while limited effects were found for modelling the behaviour itself.